Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T23:34:18+01:00
Zadanie 1.
a) (3x² -xy*-2y)*3x = 9x²-3x²y-6xy
b) 3x²-xy*(-2y*3x) =-6x²y+2xy²+9x³-3x²y = 9x³+2xy²-9x²y
c) (3x²-xy+-2xy)*3x = 9x³-3x²y-6x²y
d) 3x²-xy*3x+-2y*3x = 3x²-3x²y-6xy

Zadanie 2.
a)
3(x²-2x+3)-2(x²-5x-1) dla x=2
3*(2²-2*2+3)-2*(2²-5*2-1) =
3*(4-4+3)-2*(4-10-1) =
3*3-2*(-7) =
9+14 = 23

b)
a(2b+b)-b(a-2ab+2²) dla a=0,1 i b= -10
0,1*(2*(-10)+(-10))-(-10)*(0,1-2*0,1*(-10)+4) =
0,1*(-30)-(-10)*(0,1+2+4) =
-3-(-10)*6,1 =
-3-(-61) =
-3+61 = 58